Bevacizumab-induced immune thrombocytopenia in an ovarian cancer patient with mixed connective tissue disease: case report and literature review - Zhang, Yunting; Yang, Fanchun; Wang, Jining; Fu, Hui; Shen, Fuming; Liu, Jie; Li, Dongjie (Frontiers in Immunology, 2024)
Drug-induced immune thrombocytopenia is an adverse reaction marked by accelerated destruction of blood platelets. In cancer therapy, thrombocytopenia has many other causes including bone marrow suppression induced by chemotherapeutic agents, infection, and progression of cancer; drug-induced thrombocytopenia can easily be misdiagnosed or overlooked. Here, we present a case of an ovarian cancer patient with a history of mixed connective tissue disease who underwent surgery followed by treatment with paclitaxel, cisplatin, and bevacizumab. The patient developed acute isolated thrombocytopenia after the sixth cycle. Serum antiplatelet antibody testing revealed antibodies against glycoprotein IIb. After we analyzed the whole therapeutic process of this patient, drug-induced immune thrombocytopenia was assumed, and bevacizumab was conjectured as the most probable drug. Thrombocytopenia was ultimately successfully managed using recombinant human thrombopoietin, prednisone, and recombinant human interleukin-11. We provide a summary of existing literature on immune thrombocytopenia induced by bevacizumab and discuss related mechanisms and triggers for drug-induced immune thrombocytopenia. The present case underscores the potential of bevacizumab to induce immune-mediated thrombocytopenia, emphasizing the need for heightened vigilance towards autoimmune diseases or an autoimmune-activated state as plausible triggers for rare drug-induced immune thrombocytopenia in cancer therapy.